2021
DOI: 10.1186/s43141-021-00143-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of F-box proteins in Macrophomina phaseolina and comparison with other fungus

Abstract: Background In fungi, like other eukaryotes, protein turnover is an important cellular process for the controlling of various cellular functions. The ubiquitin-proteasome pathway degrades some selected intracellular proteins and F-box proteins are one of the important components controlling protein degradation. F-box proteins are well studied in different model plants however, their functions in the fungi are not clear yet. This study aimed to identify the genes involved in protein degradation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Besides, it was revealed that the rice HSFs gene is not intron-less, contrary to the general finding that roughly 20% of rice genes are intron-less [ 19 , 41 ]. Intron-less genes have been found in several rice transcription factors such as MADS box [ 42 ], C2H2 zinc finger [ 43 ], bZIP [ 44 ], SAUR [ 45 ] and F-box [ 46 ] gene families. Alternative splicing may occur and vary according to environmental stresses and at certain developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it was revealed that the rice HSFs gene is not intron-less, contrary to the general finding that roughly 20% of rice genes are intron-less [ 19 , 41 ]. Intron-less genes have been found in several rice transcription factors such as MADS box [ 42 ], C2H2 zinc finger [ 43 ], bZIP [ 44 ], SAUR [ 45 ] and F-box [ 46 ] gene families. Alternative splicing may occur and vary according to environmental stresses and at certain developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…One F-box gene was intronless. Fbox protein of Macrophomina phaseolina contained > 50% of the total genes to be intron-less that might have originated due to gene duplication or reverse transcription and integration (Kaessmann et al, 2009;Powell et al, 2008;Sadat et al, 2021). In Chickpea, the intron-exon structure of subfamilies had a strong structural relationship between the F-box proteins (Gupta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…F-box proteins are found in quite a few pathogenic fungi. In the hemibiotrophic fungus Magnaporthe oryzae, the F-box protein is crucial for conidiogenesis, fungal growth and development, and for virulence [ 49 ]. Suppression of these proteins could result in suppression of the growth, development, and pathogenicity of the fungal host.…”
Section: Discussionmentioning
confidence: 99%